Pendampingan Adopsi Aplikasi Digital Majoo pada UMKM Kuliner Kedai Huo Samarinda - Rohana Nur Aini; Arini Hudaya; Naila Farras Safa Aisyah; Qanita Khairunnisa Darwis; Shafa Niswa Az-zahra (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
The digitalization of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector is essential for improving operational efficiency in the digital economy era. This community service activity aimed to assist Kedai Huo, a culinary MSME in Samarinda, in adopting and optimizing the Majoo digital cashier application. The approach included field visits, participatory observation, and focused discussions with employees and managers. The results showed that the Majoo application significantly assisted in financial management, digital menu management, real-time transaction recording, and PIN-based employee attendance. However, challenges were identified, including internet connectivity dependency, limited employee access for order cancellations, and the absence of promotional features. This mentoring activity contributed positively to enhancing human resource capacity in operating digital technology and supporting gradual digital transformation within culinary MSMEs.